3log42log45+log42=
\( \frac{\log_45+\log_42}{3\log_42}= \)
\( \frac{\log_311}{\log_34}+\frac{1}{\ln3}\cdot2\log3= \)
\( \frac{2\log_78}{\log_74}+\frac{1}{\log_43}\times\log_29= \)
\( -3(\frac{\ln4}{\ln5}-\log_57+\frac{1}{\log_65})= \)
\( \frac{\log_76-\log_71.5}{3\log_72}\cdot\frac{1}{\log_{\sqrt{8}}2}= \)
\( \frac{\log_47\times\log_{\frac{1}{49}}a}{c\log_4b}= \)
\( \frac{\log_8x^3}{\log_8x^{1.5}}+\frac{1}{\log_{49}x}\times\log_7x^5= \)
\( \log_x16\times\frac{\ln7-\ln x}{\ln4}-\log_x49= \)
\( \frac{\log_x4+\log_x30.25}{x\log_x11}+x=3 \)
\( x=\text{?} \)
\( \frac{1}{\log_{2x}6}\times\log_236=\frac{\log_5(x+5)}{\log_52} \)
\( x=\text{?} \)